UJI ADAPTASI BEBERAPA VARIETAS KEDELAI (Glycine max ( L) Merril) DENGAN VARIASI PAKET TEKNOLOGI PEMUPUKAN - Mohamad Fadli; Syahrani; Rakhmadhani Norhaq; Sari Ad'mawati (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2022)
This study used split plot design arrenged in 4x3 factorial consisting of 2 factors and repeated 3 times. first factor was soybean varieties (V) which is the main plot consisted of 3 levels ie v1 (Anjasmoro varieties), v2 (Burangrang varieties), v3 (Demas1 varieties). The second factor was the variation of fertilizer technology package (P) as sub plot consisted of 4 levels. the fertilization treatment consisted of p1 (urea 25 kg ha-1 + SP-36 100 kg ha-1 + KCl 50 kg ha-1), p2 (urea 37,5 kg ha-1 + SP-36 150 kg ha-1 + KCl 75 kg ha-1), p3 (chicken manure 5 t ha-1 + urea 25 kg ha-1 + SP-36 100 kg ha-1 + KCl 50 kg ha-1), p4 (chicken manure 5 t ha-1 + urea 37.5 kg ha-1 + SP-36 150 kg ha-1 + KCl 75 kg ha-1). The results showed that the treatment of soybean varieties had no significantly effect to the average parameters age of flowering plants, harvest age, number of pods, 100 seeds of crops, weight of 100 seeds and per hectare yield but significant effect on the number of branches of crops. The highest yield per hectare was obtained in Burangrang variety with 2.06 t ha-1 yield and the lowest yield on Demas1 variety with yield of 1.51 t ha-1. Treatment of variation of fertilizer technology package had no significantly effect to all treatments. The highest yield of plant per hectare was obtained at the treatment of p2 (urea 37.5 kg ha-1 + SP-36 150 kg ha-1 + KCl 75 kg ha-1) ie 2.01 and the lowest average yield on p4 (chicken manure 5 t ha-1 + urea 37.5 kg ha-1 + SP-36 150 kg ha-1 + KCl 75 kg ha-1) with yield of 1.71 t ha-1. The interaction between several varieties and variations of fertilization had no significant effect to the average age of flowering plants, number of pods, the weight of dry seeds of the crops, weight of 100 seeds and yield per hectare (ha-1). The highest yield per hectare was obtained in v2p3 treatment (Burangrang varieties and chicken manure technology package 5 t ha-1 + urea 25 kg ha-1 + SP-36 100 kg ha-1 + KCl 50 kg ha-1) with yield 2,32 t ha-1 and lowest yield on v3p4 treatment (Demas1 variety and chicken manure technology package 5 t ha-1 + urea 37,5 kg ha-1 + SP-36 150 kg ha-1 + KCl 75 kg ha-1) with the result of 1.38 t ha-1.